Two lunar meteorites, Yamato-791197 and -82192: REE abundances and geochronological dating - Takahashi, Kazuya; Masuda, Akimasa (1987)
P(論文) Four antarctic meteorites (ALHA81005,Y-791197,-82192 and -82193) have been identified as lunar meteorites. We investigated the REE, Rb, Sr and Ba abundances and major element compositions in specimens spearated from Y-791197 and -82192. Furthermore, we have discussed the genesis of these lunar meteorites, using Rb-Sr systematics and Nd isotope ratios. Most REE patterns show similar features, reflecting those of anorthosites, and also show positive Ce anomalies. These Ce anomalies are considered to have been formed 3.9-4.0 b. y. ago, based on the age obtained from the Rb-Sr systematics for Y-791197 and -82192,55A. It is possible that these Ce anomalies could have been formed by an oxic alteration (T. TANAKA et al., Papers presented to the 10th Symp. Antarct. Meteorites, 129,1985) and this event might be related to the observation that the initial ^<87>Sr/^<86>Sr ratios are significantly low. Y-82192,63B shows a glassy feature and an age of 0.71 b. y. has been obtained from the Rb-Sr systematics for this sample. This age could indicate an event of impact partial melting (possibly, related with the formation of a crater on the moon). The Sm-Nd systematics of Y-82192,55A suggests that the REE abundances of this meteorite were differentiated from the chondritic abundances at the age 3.9 b. y. obtained from the Rb-Sr systematics. Based on the Sm-Nd data, the original formation of the parent materials of this meteorite could be traced back to around 4.3 b. y. ago. departmental bulletin paper